Australian Salt Import Policy in Indonesia: An Analysis of Public Policy - Fajrin Hardinandar; Firmansyah Firmansyah (Agriekonomika, 2023)
The purpose of this study is to examine how economic variables such as the Import of Australian Salt, Domestic Salt Consumption, Domestic Salt Production, GDP Industrial Sector consisting of textile, leather, and pharmaceutical Industry, Cost Insurance Freight (CIF), Australian Dollar Exchange Rate, and non-economic variables respond to the enactment of Government Regulation Number 9 of 2018. The method used is the Feasible Generalized Least Square (FGLS) by observing the dynamic relationship between independent and dependent variables in quarterly data from 2010 to 2021. The results show that Australia's salt imports are smaller than before the enactment of PP No. 9 of 2018. Second, public policy choices in international trade politics for the case of salt imports still prioritize economic benefits (economic scale). Third, the test results show that even though the CIF of imported salt increases, it is inelastic to a decrease in demand. Lastly, the study states that if domestic demand for salt increases with the assumption that national salt production increases, Australian salt imports can be reduced. Our short suggestions are first, the government needs to invest in physical and human technology to reform salt production technology.